Intra-stadial tick-borne Thogoto virus (Orthomyxoviridae) transmission: accelerated arbovirus transmission triggered by host death. - Wang, H; Nuttall, P (2001)
Haematophagous insect vectors of arthropod-borne viruses (arboviruses) feed repeatedly. Consequently, they can transmit arboviruses to more than one host during the same developmental stage (intra-stadial transmission). By contrast, ixodid ticks generally feed only once at each parasitic stage (larva, nymph, and adult) and hence they have only one opportunity for tickborne virus transmission per stadium (inter-stadial transmission). Under natural conditions, tick-infested hosts may die (from disease or other causes) before the ticks have completed their long period of engorgement. A laboratory model was used to investigate the consequences of premature host death on tick-borne virus transmission. We report intra-stadial transmission of Thogoto virus by the nymphal, male, and female ticks of Rhipicephalus appendiculatus. Tick-borne Thogoto virus infection caused viraemia and death of hamsters before the nymphal and adult ticks feeding on them had completed engorgement. The resulting partially fed ticks were allowed to continue engorgement on new, uninfected hosts (interrupted feeding). During feeding on the subsequent hosts, they transmitted the virus intra-stadially to susceptible hosts (hamsters), and to uninfected co-feeding ticks on non-susceptible hosts (guinea-pigs). Intra-stadial transmission, mediated by interrupted feeding, may help explain outbreaks of rapid and fatal tick-borne viral diseases, and the epidemiology as well as evolution of virulence, in a susceptible host population. Additionally, intra-stadial transmission provides an increased risk of tick-borne pathogen transmission to humans and domestic animals during slaughter and game hunting.